Mathematical modeling of Elbrus glaciers in the 21st century. Part 1. Glaciological model and setup of numerical experiments. - T. N. Postnikova; O. O. Rybak; A. S. Gubanov; H. Zekollari; M. Huss (Лëд и снег)
This study fills a gap in the long-term prediction of changes in parameters of the Elbrus glaciers, using the GloGEMflow-debris model to simulate the glacier evolution. The part 1 provides a detailed description of the model architecture. The model consists of three blocks in which the calculation of the surface mass balance, glacier flow and moraine transformation is carried out. The area and thickness of the moraine cover increase as glaciers degrade. This is important to consider, as a thicker layer of moraine reduces the ice melting. For predictive calculations, the data on temperature and precipitation for five SSP climate scenarios are taken from the CMIP6 project. A temperature index method is used to calculate the surface mass balance, taking into account the influence of the moraine cover: the ablation of pure ice is adjusted in accordance with the area and thickness of the moraine cover. The ice flow block is used to update the geometry of glaciers and moraine cover. The adaptation of the model to the glaciers of Elbrus includes the adjustment of the block of the moraine cover evolution, which corresponds to the geological features of the region. Thus, the accumulation of moraine on the glaciers of the volcanic peak through erosion of slopes and landslides can be neglected, it is considered to be the bottom moraine, thrown up along the shear planes, the main source of surface moraine on the glaciers of Elbrus. Hence, the debris-cover source in the model is specified to be the result of bedrock erosion rather than slope erosion. The paper discusses calibration processes that allow using simple modeling methods, such as the temperature index method for calculating the surface mass balance, and to simulate the real behavior of glaciers. Despite the fact that the validation of the model revealed a slight underestimation of mass loss at the beginning of the XXI century, the general patterns of mass loss are reproduced correctly, although the energy balance has not been explicitly described. Thus, the adjustment of the model ensures its adaptation to the glaciation conditions on Elbrus.